2011
DOI: 10.2174/1874914301104010096
|View full text |Cite
|
Sign up to set email alerts
|

Elections in Botswana: A Ritual Enterprise?

Abstract: Botswana has the reputation of being Africa's longest surviving democracy having held uninterrupted elections at five year intervals since the pre-independence elections of 1965. The latest elections were held in October 2009. Although in democratic discourse it is assumed and/or expected that the holding of regular free, fair and competitive multiparty elections should provide an opportunity of regime change, this has so far not materialized in Botswana. The country is therefore a dominant-party system with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Khama was brought into politics by former president Festus Mogae with the view to ending factionalism within the BDP (Taylor, 2005b). However, it appears factionalism within the BDP has intensified under Khama’s leadership and he has, for unknown reasons, become associated with one of the factions in the party (Botlhomilwe and Sebudubudu, 2011). Instead of uniting the party, he largely manages it by advocating a compromise list, as opposed to holding elections for the executive positions of the party.…”
Section: Contradictions Of Botswana’s Successmentioning
confidence: 99%
See 1 more Smart Citation
“…Khama was brought into politics by former president Festus Mogae with the view to ending factionalism within the BDP (Taylor, 2005b). However, it appears factionalism within the BDP has intensified under Khama’s leadership and he has, for unknown reasons, become associated with one of the factions in the party (Botlhomilwe and Sebudubudu, 2011). Instead of uniting the party, he largely manages it by advocating a compromise list, as opposed to holding elections for the executive positions of the party.…”
Section: Contradictions Of Botswana’s Successmentioning
confidence: 99%
“…However, a military background is not necessarily an impediment to embracing democratic values. As Botlhomilwe, Sebudubudu and Maripe (2011: 345) remind us, ‘Experience has shown that even people who have been confined to total institutions have successfully re-entered conventional society,’ The other possible reason for his undemocratic tendencies is the fact that he wielded too much power before reaching the age of maturity. To be appointed a Brigadier in the army at the age of 24 is not a common occurrence in world armies.…”
Section: Contradictions Of Botswana’s Successmentioning
confidence: 99%